A Zero-Voltage-Transition H5-Type Transformerless Photovoltaic Grid-Connected Inverter - Jicheng Fang; Mingming Shi; Huafeng Xiao; Ruibin Wang (IEEE Access)
Efficiency and leakage current are two major issues for transformerless grid-connected inverters (TLI). Soft-switching technology can reduce switching losses, and is a good choice for high-frequency TLIs. Herein, a zero-voltage-transition H5 type (ZVT-H5) inverter with soft turn-on and turn-off transitions for high-frequency main switches is derived from basic resonant tanks in this paper. Meanwhile, the reverse recovery problem of freewheeling diodes is alleviated under the operation of the auxiliary resonant network. As a result, the conversion efficiency of ZVT-H5 can be significantly improved comparing with hard-switching H5 (HS-H5) inverter. Moreover, a diode clamping branch is employed to achieve constant common-mode characteristic for the ZVT-H5. The construction process of the proposed topology is described, and the operation principle of the auxiliary resonant network is analyzed. In addition, the resonant parameter design of ZVT-H5 and its circuit performance are discussed in detail. Finally, the experimental results of a 3-kW prototype at 100 kHz switching frequency are provided to verify the effectiveness of the ZVT-H5.